PEMAHAMAN SYAIR TEMBANG LIR-ILIR KARYA SUNAN KALIJAGA DALAM PEMBELAJARAN IPS PADA SISWA KELAS VII B SMP KRISTEN SATYA WACANA SALATIGA - Daniel Zafnat Paaneah; Sunardi Sunardi; Emy Wuryani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2019)
Song Lir-ilir is one of the legacies in the form of music art in the time of Islam by Sunan Kalijaga, which at that time was used as a media to spread Islam. In social studies learning, on 7th grade junior high school has material about the period of Islam in Indonesia which is the material also discusses the relics of the Islamic period in Indonesia. But students do not yet know that Lir-ilir song is one of them and play an important role in the process of Islamization in Indonesia and meaning that are able to educate students's character. The purpose of this study is to explain students's understanding, character arising and the effect of Lir-ilir songs on students. This research was carried out on students 7th grade Class B of SMP Kristen Satya Wacana Salatiga 2nd semester year of 2018/2019, totaling 22 students. In the pre-test of this study students got an average of 7.9 which can be concluded that students do not understand or recognize Lir-ilir songs. In learning students are taught about the meaning and understanding of the song that teaches the value of tolerance and mutual respect, for fellow examples in the scope of the school; bullying, etc. Students also learned to sing Lir-ilir song in front of the class in groups. On the post-test average value of students's understanding increases to 90 so it can be concluded that students become undestand of the song Lir-ilir.